Histone H3 Lysine 56 Acetylation Is Required for Formation of Normal Levels of Meiotic DNA Breaks in S. cerevisiae - Karányi, Zsolt; Hornyák, Lilla; Székvölgyi, Lóránt (Frontiers in Cell and Developmental Biology, 2020)
Meiotic recombination is initiated by Spo11-catalyzed DNA double-strand breaks (DSBs) that are promoted by histone modifications and histone modifying enzymes. Herein we investigated the role of histone H3 lysine 56 acetylation (H3K56ac) located near the entry/exit points of the DNA in the globular H3 domain. We generated a series of mutant cells (asf1Δ, rtt109Δ, hst3/4Δ, and H3K56A) in which the endogenous level of H3K56ac was manipulated and tracked during meiotic growth. We show that complete loss or increased abundance of H3K56ac in these mutants allows timely entry into meiosis and sporulation and does not impair S phase progression, first and second meiotic cell divisions, and spore viability. In the asf1Δ, rtt109Δ, hst3/4Δ mutants, DSBs and crossovers form normal levels with a short (60-min) delay at the HIS4-LEU2 artificial recombination hotspot, however, DSB formation shows a ~3-fold decrease in the H3K56A mutant at the natural BUD23-ARE1 hotspot. The latter DSB phenotype, showing significant DSB reduction in the H3K56A mutant, was also observed at DSB sites using genome-wide mapping of Rfa1-coated single-stranded DNA flanking DSBs (RPA ChIP). Parallel mapping of H3K56-acetylated histones in wild type cells revealed strong depletion of the H3K56ac ChIP signal over Spo11-oligo DSBs, albeit most H3K56-acetylated histones were enriched adjacent to the identified RPA ChIP binding sites. Taken together, these associations demonstrate a prominent role of H3 lysine 56 acetylation in the formation of DNA breaks within recombination hotspot regions.